Analysis of Medicine Management in the Pharmacy Installation at Hospital X of Tomohon City - Rumagit, Hanna M.; Montolalu, Friska M.; Timburas, Mitra W. (FMIPA UKIT, 2024)
This study aims to analyze the efficiency of medicine management at Hospital X in Tomohon City by evaluating such indicators as selection, procurement, distribution, and use of drugs. It employed a descriptive method to examine retrospective data gleaned from interviews to assess the compliance of medicine management with the standards set by the Indonesian Ministry of Health, WHO, and Regulations of the Ministry of Health. The results indicated that the selection phase only reached 55.65% compliance with the National Formula, while procurement showed a budget allocation of 25.08%, which was below the standard. The distribution of drugs demonstrated full compliance on several indicators, such as the percentage of physical drug matching with stock cards (100%) and documentation error frequency (0%). Drug use showed varied outcomes in that antibiotic prescribing reached 30.2%, exceeding the WHO standard of ?22.7%. To some extent, this indicated potential irrationality. The study concludes that while the distribution and some aspects of procurement have satisfied the standards, the selection and use of drugs require improvement to enhance efficiency and regulatory compliance.